The Role of Land Deed Officers in the BPHTB Payment Verification Process - Fadhla Audina; Taufan Fajar (Sultan Agung Notary Law Review, 2021)
PPAT plays an important role in the sale and purchase of land, which has indirectly helped the Head of Regency/City BPN to carry out activities related to land. PPAT's position is very important in the delivery of transaction prices as the basis for determining BPHTB to the public. The deed of sale and purchase is made when the object and the transaction price have been agreed upon and have been paid in full by the buyer, but before that, tax verification must be carried out as the main requirement in the land sale and purchase transaction. A potential source of tax that should be explored according to the current economic situation and condition as well as the development of the nation's development is the type of Customs Tax on the Acquisition of Land and Building Rights (BPHTB). Fee for the acquisition of land and building rights, hereinafter abbreviated as BPHTB, is a tax on the acquisition of land and building rights. The role of the Land Deed Maker Officer in the verification process for BPHTB payments in Batang City is to examine and supervise the signing of the deed. BPHTB tax collection exists because of the transfer of rights to land and buildings so that PPAT will make a deed of sale if the taxpayer pays the BPHTB tax first. The Land Deed Maker official plays a very important role in the verification process of BPHTB payments for sale and purchase transactions of land and building rights in Batang City.